2020
DOI: 10.3389/fcimb.2020.00316
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Non-coding RNA Profiles of Exosome-Like Vesicles From the Protoscoleces and Hydatid Cyst Fluid of Echinococcus granulosus

Abstract: Cystic echinococcosis is a worldwide chronic zoonotic disease that threatens human health and animal husbandry. Exosome-like vesicles (ELVs) have emerged recently as mediators in the parasite-parasite intercommunication and parasite-host interactions. Exosome-like vesicles from parasites can transfer non-coding RNAs (ncRNAs) into host cells to regulate their gene expression; however, the ncRNAs profiles of the ELVs from Echinococcus granulosus remain unknown. Here, we isolated protoscolece (PSC)-ELVs and hydat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 65 publications
2
39
0
Order By: Relevance
“…At present, the relevance of lncRNA to the pathogenesis, host resistance, and parasite evasion during parasitic infection is emphasized [ 34 ]. There is increasing attention to the contribution of lncRNA to E. granulosus infection [ 35 ]. This kind of research will contribute to the reasonable design of immune therapy and vaccination schemes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the relevance of lncRNA to the pathogenesis, host resistance, and parasite evasion during parasitic infection is emphasized [ 34 ]. There is increasing attention to the contribution of lncRNA to E. granulosus infection [ 35 ]. This kind of research will contribute to the reasonable design of immune therapy and vaccination schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Although lncRNAs have a variety of biological functions, the range of potential biological functions of lncRNAs in parasitic infection is vast and still largely unexplored [ 33 , 34 ]. A recent study found that microRNA (miRNA), lncRNA, and circular RNA (circRNA) had been identified in protoscoleces exosome-like vesicles and hydatid fluid, and was predicted to participate in the parasite-host interactions [ 35 ]. Therefore, identifying how lncRNA regulates CD4 + T cell differentiation could provide new mechanistic insights and therapeutic targets for CE.…”
Section: Introductionmentioning
confidence: 99%
“…The release of tRNAs and/or tRFs to extracellular compartments has been documented in organisms across all kingdoms ( Bayer-Santos et al, 2014 ; Lambertz et al, 2015 ; Peres da Silva et al, 2015 ; Tsatsaronis et al, 2018 ; Alves et al, 2019 ; Tosar and Cayota, 2020 ; Wang et al, 2021 ). Full length tRNAs constitute a large part of the RNAs found in EVs in many studies ( Nolte-’t Hoen et al, 2012 ; Zhang et al, 2020 ; Tosar et al, 2015 ; Shurtleff et al, 2017 ). For instance, over-representation of tRNAs has been observed in EVs released by breast cells, bone marrow and adipose-mesenchymal stem cells, lung cells, and EVs from biofluids ( Vojtech et al, 2014 ; Baglio et al, 2015 ; Tosar et al, 2015 ).…”
Section: Trnas and Trfs Are Abundant Components Of The Extracellular Compartmentmentioning
confidence: 99%
“…At present, the relevance of lncRNA to the pathogenesis, host resistance and parasite evasion during parasitic infection is emphasized [35]. There is increasing attention to the contribution of lncRNA to E. granulosus infection [36]. This kind of research will contribute to the reasonable design of immune therapy and vaccination scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Although lncRNAs have a variety of biological functions, the knowledge of the potential biological functions of lncRNAs in parasitic infection is still vast and largely unexplored [34,35]. A recent study found that microRNA (miRNA), lncRNA, and circular RNA (circRNA) had been identi ed in protoscoleces exosome-like vesicles and hydatid uid, and was predicted to participate in the parasite-host interactions [36]. Therefore, identifying how lncRNA regulates CD4 + T cell differentiation could provide new mechanistic insights and therapeutic targets for CE.…”
mentioning
confidence: 99%